The LEGO® neighborhood book. 2, Build your own city! - Lyles, Brian; Lyles, Jason (No Starch Press, Inc., 2019)
Step-by-step instructions show how to build detailed LEGO models of neighborhoods - complete with homes, stores, restaurants, barbershops, and more. Enter the fantastical world of model building. The LEGO Neighborhood Book 2 is a full-color guide to creating intricate, bustling LEGO neighborhoods, and cities. In this second volume, a follow up to the runaway best-selling first volume, readers learn even more ways to create classic architectural styles using only LEGO bricks. In addition to creating entire buildings, LEGO model-building experts Brian and Jason Lyles also show readers how to create interesting architectural features like cornices, false fronts, porches, and detailed interiors and furniture. With instructions for three buildings and many smaller builds, The LEGO Neighborhood Book 2 is sure to provide hours of building fun and inspiration for readers of all ages.